Efektivitas Cognitive Behavior Therapy dan Psikoedukasi Keluarga dalam Menurunkan Perilaku Menentang pada Remaja dengan Riwayat Trauma Pengasuhan: Studi Kasus - Nazarlin Nazarlin; Sri Novia Martin; Melati Putri Ulandari; Rizkia Maghfirah; Aflah Zakinov Irta (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study aimed to examine the effectiveness of Cognitive Behavioral Therapy (CBT) and family psychoeducation in reducing oppositional behavior among adolescents with a history of developmental relational trauma. The participant was a 17-year-old male adolescent who exhibited symptoms of irritability, emotional sensitivity, social withdrawal, interpersonal conflicts in a residential care setting, and difficulties in emotion regulation. Data were collected through clinical interviews, behavioral observations, graphic psychological tests, the Sack's Sentence Completion Test (SSCT), and intervention outcome evaluations. The assessment revealed maladaptive cognitive schemas characterized by dysfunctional core beliefs such as "I have been abandoned," "My family does not care about me," and "People are against me." These negative beliefs contributed to persistent anger, avoidance behaviors, emotional dysregulation, and oppositional responses toward authority figures and social rules. Cognitive Behavioral Therapy was delivered across five structured sessions to assist the participant in identifying automatic negative thoughts, restructuring maladaptive cognitions, developing adaptive emotion regulation strategies, practicing relaxation techniques, and enhancing constructive behavioral responses. In addition, family psychoeducation was provided to the caregiver and residential care staff to improve their understanding of the adolescent's psychological condition, strengthen social support, and foster a more supportive caregiving environment. Following the intervention, the participant demonstrated increased self-awareness, improved ability to identify emotional triggers, greater openness in interpersonal communication, and more adaptive emotional and behavioral regulation. Enhanced support from caregivers and the residential environment also contributed to the participant's psychological adjustment. These findings underscore the importance of integrating individual cognitive-behavioral interventions with systemic family-based approaches in managing oppositional behavior among adolescents with histories of relational trauma and adverse childhood experiences.